Oxidative stress promotes lipid-laden macrophage formation via CYP1B1 - Yin Zhu; Saugata Dutta; Yohan Han; Dooyoung Choi; Francesca Polverino; Caroline A. Owen; Payaningal R. Somanath; Xiaoyun Wang; Duo Zhang (Redox Biology)
Emerging evidence suggests that lipid-laden macrophages (LLM) participate in lung damage in various clinical conditions. However, the mechanisms involved in LLM formation are not fully understood. In this study, we aimed to investigate the link between reactive oxygen species (ROS) and LLM formation. We found that ROS triggered by cigarette smoke extract (CSE) or H2O2 significantly promoted LLM formation. Given the key role of ROS in LLM formation, we further demonstrated that LLM formation is induced by various ROS-producing stimuli, including bacteria, oxidized low-density lipoprotein (OxLDL), hyperoxia, and E-cigarette vapor extract (EVE). Meanwhile, cytochrome P450 family-1 subfamily B member 1 (CYP1B1) was highly upregulated in lung macrophages from chronic obstructive pulmonary disease (COPD) patients and CSE-treated macrophages. Functionally, CYP1B1 contributes to the CSE-induced lipid accumulation and LLM formation. CYP1B1 expression and LLM formation were effectively suppressed by antioxidant N-acetylcysteine (NAC) and carvedilol. The formation of LLM was also associated with classically activated M1 but not the M2 state. CSE-induced LLM showed time-dependent alterations in inflammatory response and phagocytic ability. In summary, our study highlights the role of oxidative stress in LLM formation. CYP1B1 contributes to ROS-induced LLM formation and may serve as a therapeutic target for reducing LLM-induced lung damage.